Quantifying consumer preferences - Slottje, Daniel Jonathan, 1957- (Contributions to economic analysis ;, 2009)
This volume presents straightforward, innovative research on the estimation of demand systems and the measurement of consumer preferences. Demand studies and understanding consumer behavior remain two of the most important areas of analysis by practicing applied economists and econometricians. This volume also offers state of the art research in demand analysis, using modern econometric tools to analyze consumer behavior and estimate demand relationships for well known demand systems. This book will be aimed at a broad audience of economists and other social scientists; including generalists, graduate students, private sector economists and others.